Perancangan Game Edukasi Pembelajaran Ilmu Tajwid dengan Mengimplementasikan Algoritma Fisher-Yates dan Flood Fill - Ricky Syah Putra; Septi Andryana; Rima Tamara Aldisa (KITA Institute, 2022)
In this day and age, children cannot be separated from their cellphones. The role of parents in the use of mobile phones for children is very important. By making learning media using smartphones that can add knowledge, especially in Islam, it is hoped that it can help the millennial generation in learning Islam. Mobile-based educational applications are expected to increase children's motivation or enthusiasm for learning at an early age to elementary school children so that they can recognize good and correct basic tajwid knowledge. The purpose of this author is to Design an educational Game of tajwid science for children aged 7-12 years to get to know the basics of recitation by using the drag and drop method with the placement of controls on random questions In this Game with the Fisher-Yates algorithm to randomize practice questions, this application displays 20 questions randomly, and applies the Flood Fill algorithm to color images or objects. This Game was made in order to increase broad knowledge and increase knowledge for children who do not understand the science of recitation in the Qur'an.